2009
DOI: 10.1103/physrevlett.103.156804
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Hall Plateau Transition in Graphene with Spatially Correlated Random Hopping

Abstract: We investigate how the criticality of the quantum Hall plateau transition in disordered graphene differs from those in the ordinary quantum Hall systems, based on the honeycomb lattice with ripples modeled as random hoppings. The criticality of the graphene-specific n = 0 Landau level is found to change dramatically to an anomalous, almost exact fixed point as soon as we make the random hopping spatially correlated over a few bond lengths. We attribute this to the preserved chiral symmetry and suppressed scatt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
42
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 40 publications
5
42
1
Order By: Relevance
“…In particular, the inclusion of a finite correlation length on the hopping (off-diagonal) disorder model was recently reported to induce an anomalously sharp n = 0 LL compared to higher levels. 25,26 It was found that the width of the zeroth LL (Γ 0 ) shrinks to zero as soon as the hopping correlation length λ exceeds the lattice parameter a, in line with analytical studies of the effects of long-range chiral disorder.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…In particular, the inclusion of a finite correlation length on the hopping (off-diagonal) disorder model was recently reported to induce an anomalously sharp n = 0 LL compared to higher levels. 25,26 It was found that the width of the zeroth LL (Γ 0 ) shrinks to zero as soon as the hopping correlation length λ exceeds the lattice parameter a, in line with analytical studies of the effects of long-range chiral disorder.…”
Section: Introductionmentioning
confidence: 82%
“…[21][22][23][24][25][26][27][28][29] The broadening of the LLs differs among disorder models. In particular, the inclusion of a finite correlation length on the hopping (off-diagonal) disorder model was recently reported to induce an anomalously sharp n = 0 LL compared to higher levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Yet, which type of disorder is encountered in real samples is still completely unclear or only partly known in some special cases. This lack of knowledge is particularly unfortunate as the definite type of disorder entirely determines the physical properties, 15,16,17,18,19,20,21 e.g., leading to complete Anderson localization in the case of short range electrostatic scattering potentials via chiral symmetry breaking and scattering between valleys. 22,23 For disordered systems, even the single particle density of states (DOS) near the Dirac point remains still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the effect on the n = 0 Landau level, which is essential to the anomalous Hall effect of massless Dirac fermions, is examined from the viewpoint of the fermion doubling and the symmetry of the system. In our previous work 12 , we have shown that the n = 0 Landau level of the honeycomb lattice (graphene) becomes anomalously sharp even in the presence of disorder, if the disorder respects the chiral symmetry and is spatially correlated over a distance exceeding a few lattice constants. Conversely, we have also pointed out that when the disorder is spatially uncorrelated, the n = 0 Landau level is broadened just like the other Landau levels, even if the chiral symmetry is respected by the disorder.…”
Section: Introductionmentioning
confidence: 99%